Blackboard Facilities and Activities in an English Linguistics Course for Professional Business Communication before, during and after the Outbreak of Covid-19 - Costanza Cucchi (MediAzioni)
The present study describes the organisation of an English Linguistics course for Professional Business Communication targeting students of modern languages with reference to the facilities utilised in Blackboard, the university learning platform, before, during and after the sudden outbreak of the Covid-19 pandemic. In particular, it is shown how the teaching activities which had been previously performed in-person were modified in February 2020 to suit remote online teaching, and how this shaped the following editions of the course, which were delivered in dual-mode (2021/22) and in-person (2022/23 and 2023/24). The students’ perceptions of the activities were examined through two questionnaires: the first administered after the first remote online course and the second after the dual-mode courses. Overall, results show that the pandemic provided a chance to introduce activities and tools, such as wikis, forums and reflective journals, which were considered beneficial by students, as well as to use a wider range of Blackboard facilities.